The impact of temporary contracts on gross job and worker flows - Mahmood Arai; Fredrik Heyman (Stockholm School of Economics, The Economic Research Institute (EFI), 2002)
Based on direct information on hires and separations for 11.000 establishments during 11 years, we report new evidence that around half of job and worker flows stem from temporary contracts which account for only around 10 percent of employment. The share of temporary contracts is positively correlated to employment growth indicating that firms use temporary jobs as a buffer in labor adjustment. Job reallocation for temporary contracts is acyclical. Service establishments with a high share of temporary employment exhibit acyclical job reallocation while permanent jobs in manufacturing are countercyclical.
Keywords: J21; J23; 330; Job Creation and Job Destruction; Worker Flows; Dual Labor Markets; Temporary Employment; Befristeter Arbeitsvertrag; Beschäftigungseffekt; Arbeitsmobilität; Schweden